The relationship between walkability and landscape values in transportation. Examination of landscape values in urban area transportation axes - Pirselimoğlu Batman, Zeynep; Ender Altay, Elvan; Şengül, Sena (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The existence of pedestrian areas in transportation integrate with the natural, cultural and social environment. In these areas the activities and uses in the neighborhood or around the neighborhood, accessibility, structuring of neighborhood street networks, pedestrian safety, attractiveness of the streets for users and user density of the streets are the most important components. Transportation systems in cities should be planned with landscape values linked to the urban identity, considering that the connected systems and walkable areas integrated with these areas are a part of the city. The aim of the study is to reveal the landscape values of walkable areas in vehicle-pedestrian based transportation axes and to reveal the potential of the area. In this context, the landscape values of Atatürk Street, which is located in the city core of Bursa and has both touristic, social and commercial functions, in pedestrian transportation were evaluated on the basis of walkability on the sidewalks, and a partially sufficient result was reached. As a result, landscape plans should be developed that will support the use of streets that can respond to transportation values and that can be easily experienced by all user groups, where urban identity is emphasized in transportation axes.